Restricting Vitamin A in cattle diets improves beef carcass marbling and USDA quality and yield grades - Arnett, A.M.; Daniel, M.J.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Marbling continues to be a major factor affecting profitability for beef producers, processors, retailers, and restaurateurs. However, feeding animals to ‘fatten’ is quite inefficient, requiring about 2.25 times more energy than is needed for producing lean muscle. For the cattle feeding industry to be sustainable in the future, increases in marbling must be accomplished without increasing days on feed, slaughter age carcass weight, and fatness and without sacrificing feed efficiency and carcass cutability. A 2002 survey of feedlot nutritionists revealed that most recommended supplementation of vitamin A to feedlot cattle at levels exceeding the guidelines of the National Research Council (NRC) by three to five times. Because vitamin A fortification of cattle diets is an inexpensive method used to improve the immune response of receiving cattle, it is likely that few have considered the negative consequences of over-supplementing vitamin A on marbling and carcass quality grades of feedlot cattle. The objective of our research was to evaluate the effects of supplementing vitamin A at either zero (NA) or seven times (HA) the NRC-recommended level in feedlot diets and age at weaning on carcass marbling development and USDA quality grade of crossbred beef steers.
Keywords: Beef; Cattle; Marbling; Vitamin A